2021
DOI: 10.3390/jof7110931
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Enzymes as Catalytic Tools for Polyethylene Terephthalate (PET) Degradation

Abstract: The ubiquitous persistence of plastic waste in diverse forms and different environmental matrices is one of the main challenges that modern societies are facing at present. The exponential utilization and recalcitrance of synthetic plastics, including polyethylene terephthalate (PET), results in their extensive accumulation, which is a significant threat to the ecosystem. The growing amount of plastic waste ending up in landfills and oceans is alarming due to its possible adverse effects on biota. Thus, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…This technique enhances catalytic activity and increases the stability, specificity and selectivity of the immobilized enzymes, thus significantly reducing production costs [242]. A number of studies have reported that the immobilisation of PET-degrading bacterial enzymes enhances their catalytic activity and thermal stability [243][244][245], but few studies have focused on fungi [246]. Su et al [247] immobilised cutinase from Aspergillus oryzae, Humicola insolens and Thielavia terrestris on the macroporous support Lewatit VP OC 1600 obtaining immobilization yields higher than 98%.…”
Section: Conclusion and Perspectives For Future Researchmentioning
confidence: 99%
“…This technique enhances catalytic activity and increases the stability, specificity and selectivity of the immobilized enzymes, thus significantly reducing production costs [242]. A number of studies have reported that the immobilisation of PET-degrading bacterial enzymes enhances their catalytic activity and thermal stability [243][244][245], but few studies have focused on fungi [246]. Su et al [247] immobilised cutinase from Aspergillus oryzae, Humicola insolens and Thielavia terrestris on the macroporous support Lewatit VP OC 1600 obtaining immobilization yields higher than 98%.…”
Section: Conclusion and Perspectives For Future Researchmentioning
confidence: 99%
“…It is a portable device with a rechargeable battery that can be taken anywhere. The case is 3D printed and the material used was a glycolmodified version of polyethylene terephthalate (PET), which is a lightweight and strong plastic [18], [19]. The The waist and height of twenty (20) individuals composed of ten (10) males and ten (10) females were used to test the features of the device.…”
Section: Resultsmentioning
confidence: 99%
“…This transparent, durable, and lightweight plastic is widely used for packaging, including disposable drink bottles. The fungi of the genera Aspergillus , Fusarium , and Humicola [ 43 ] are involved in its degradation in nature.…”
Section: Degradation Of Some Industrial Materials By Fungimentioning
confidence: 99%